Training of Education professionals: political and social impacts of the relationship between mentors and mentees in postgraduate studies - Terezinha Oliveira (Ensaio, 2024)
This article is a reflection on the close relationship between research and the training of Education professionals. Its aim is to highlight that research in postgraduate studies affects society in all aspects, especially in Basic Education. Therefore, the training of new researchers by mentors is a key component for the development of science in the country. Given this perception, the topic needs to be explored and investigated because the relationship between mentor and mentee constitutes the heart of postgraduate studies, and its outcomes impact everyone, as evidenced by the data from Inep presented in the article. It’s important to consider that postgraduate studies, by generating science and training professors in Higher Education who train new teachers, should not be overlooked. I emphasize that the presented formulations here demonstrate my position in teaching, my political action, in which historical knowledge is the vector of communal life. Therefore, it is crucial to debate the relationship between mentor and mentee in postgraduate studies because that’s where I believe essential discussions should take place.